2006
DOI: 10.1007/s10803-006-0107-0
|View full text |Cite
|
Sign up to set email alerts
|

Introducing MASC: A Movie for the Assessment of Social Cognition

Abstract: In the present study we introduce a sensitive video-based test for the evaluation of subtle mindreading difficulties: the Movie for the Assessment of Social Cognition (MASC). This new mindreading tool involves watching a short film and answering questions referring to the actors' mental states. A group of adults with Asperger syndrome (n = 19) and well-matched control subjects (n = 20) were administered the MASC and three other mindreading tools as part of a broader neuropsychological testing session. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
734
5
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 732 publications
(764 citation statements)
references
References 44 publications
9
734
5
16
Order By: Relevance
“…In contrast, explicit video-based tasks are less structured and thus provide a more sensitive assessment of social cognitive impairments in high-functioning individuals with ASD. Using a moviebased task, Dziobek et al (2006) found that individuals with ASD were less accurate at answering explicit questions referring to the actors' mental states compared to TD controls. Moreover, the movie-based task was more sensitive in picking up mentalizing difficulties of individuals with ASD than static tasks such as the Strange Stories test or the RMET.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, explicit video-based tasks are less structured and thus provide a more sensitive assessment of social cognitive impairments in high-functioning individuals with ASD. Using a moviebased task, Dziobek et al (2006) found that individuals with ASD were less accurate at answering explicit questions referring to the actors' mental states compared to TD controls. Moreover, the movie-based task was more sensitive in picking up mentalizing difficulties of individuals with ASD than static tasks such as the Strange Stories test or the RMET.…”
Section: Discussionmentioning
confidence: 99%
“…''overmentralizing''), e.g., interpreting a mistake as intentional rather than accidental; (B) mental state inferences that are ''insufficient'' (i.e. ''undermentalizing''), e.g., underestimating the consequences of disrespectful behavior; and (C) non-mental state inferences, i.e., the inferences are not directly related to the mental states of the protagonists in the previous interaction (for a similar approach, see Dziobek et al 2006).…”
Section: The Arena Of Emotions Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…Total test scores range from 0 to 25. We also selected the Movie for Assessment of Social Cognition (Dziobek et al, 2006) to provide an ecologically valid measure of dynamic social cognition in naturalistic settings (Heavey, Phillips, Baron-Cohen & Rutter, 2000). The MASC consists of a 15 minute film depicting social interaction between four adults and is paused 45 times with participants answering questions about a character's feelings, thoughts and intentions.…”
Section: Executive Function Measuresmentioning
confidence: 99%